Philosophy for A2 : ethics and philosophy of mind - Lacewing, Michael (Routledge, 2015)
Philosophy for A2 is an engaging textbook for the new AQA A2 Philosophy syllabus. Structured closely around the AQA specification this textbook covers the two units, Ethics and Philosophy of Mind, in a comprehensive and student-friendly way. All of the anthology texts are explained and commented on and woven into the discussion of the syllabus. With chapters on 'How to Do Philosophy' and exam preparation this textbook provides students with the philosophical skills they need to succeed.